2022
DOI: 10.1021/acsabm.1c01082
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Polylactic Acid/Bamboo Fiber Composites

Abstract: The development of green and renewable materials has attracted increasing attention in recent years. Hence, biocomposite-based packaging materials have been investigated to replace petrochemical materials in several industries, such as the food packaging and electronics packaging industries. The tensile and thermal properties of biocomposite-based packaging materials composed of polylactic acid and plant fiber were mainly investigated in the current literature, but fewer studies on the improvement of water res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…This could be due to the hydrophilicity of the bamboo fiber, which plays a vital role in decreasing the contact angles. The present study depicts a similar result as mentioned in the literature [ 55 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This could be due to the hydrophilicity of the bamboo fiber, which plays a vital role in decreasing the contact angles. The present study depicts a similar result as mentioned in the literature [ 55 ].…”
Section: Resultssupporting
confidence: 93%
“…With the addition of BP, the water contact angle decreased due to the hydrophilic nature of BP. Wu et al [ 55 ] studied the wettability of bamboo fiber-reinforced PLA composites. It was found that the contact angle decreased with the increase in bamboo fiber content in the composite.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that bamboo fiber was treated with 0.1 N NaOH solution which resulted in an improvement in the interfacial properties between epoxy and fiber. Wu et al [ 16 ] developed biocomposites using Sasa longiligulata bamboo and PLA. The developed composite was tested mechanically, physically and thermally.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, with the latest awareness of the environmental impact and strict environmental regulations of governments worldwide, people have begun to pay attention to the entire life cycle of products and have been extracting biodegradable materials from renewable resources. [4][5][6] Poly(lactic acid) (PLA) is a linear aliphatic polyester extracted from renewable resources such as sugarcane and starch. It can be completely degraded into CO 2 and H 2 O with no environmental pollution, thus becoming the most promising biodegradable plastic.…”
Section: Introductionmentioning
confidence: 99%
“…But most of them are derived from fossil resources and non‐degradable. Therefore, with the latest awareness of the environmental impact and strict environmental regulations of governments worldwide, people have begun to pay attention to the entire life cycle of products and have been extracting biodegradable materials from renewable resources 4–6 …”
Section: Introductionmentioning
confidence: 99%